2019
DOI: 10.1080/0886022x.2019.1655448
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of botulinum toxin A management for neurogenic detrusor overactivity: meta-analysis

Abstract: The aim of this work was to evaluate the efficacy and safety of botulinum toxin A (BTX-A) treatment in patients with neurogenic detrusor overactivity. PUBMED, EMBASE, and Cochrane Library were identified on 13 May 2017 to identify relevant randomized controlled trials. All data obtained were analyzed using Stata 12.0. Five randomized controlled trials were included in this study. Compared to placebo, the BTX-A groups had significantly fewer urinary incontinence (UI) episodes per day and per week (BTX-A with 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…According to Cheng et al [ 46 ], the mean frequency of incontinence episodes in patients with NDO treated with onabotulinum toxin decreased significantly at week 6 post-injection as compared with placebo. Those findings are consistent with the results of other meta-analyses published by Wu et al [ 47 ], Zhou et al [ 48 ], and Yuan et al [ 49 ]. Additionally, Cheng et al [ 46 ] found no significant differences in the effectiveness of botulinum toxin administered at 200 and 300 units, which is in agreement with the results of meta-analyses published by Zhang et al [ 50 ], Wu et al [ 47 ], and Gu et al [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to Cheng et al [ 46 ], the mean frequency of incontinence episodes in patients with NDO treated with onabotulinum toxin decreased significantly at week 6 post-injection as compared with placebo. Those findings are consistent with the results of other meta-analyses published by Wu et al [ 47 ], Zhou et al [ 48 ], and Yuan et al [ 49 ]. Additionally, Cheng et al [ 46 ] found no significant differences in the effectiveness of botulinum toxin administered at 200 and 300 units, which is in agreement with the results of meta-analyses published by Zhang et al [ 50 ], Wu et al [ 47 ], and Gu et al [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Those findings are consistent with the results of other meta-analyses published by Wu et al [47], Zhou et al [48], and Yuan et al [49]. Additionally, Cheng et al [46] found no significant differences in the effectiveness of botulinum toxin administered at 200 and 300 units, which is in agreement with the results of meta-analyses published by Zhang et al [50], Wu et al [47], and Gu et al [51]. Kennelly et al [52] published the results of a long-term study analyzing the effectiveness and safety of botulinum toxin treatment during a four-year follow-up.…”
Section: Effect Of Botulinum Toxin Treatment On Qol During the Manage...supporting
confidence: 94%
“…Treatment should be tailored to the individual patient, also considering that conventional treatment programs for non-neurogenic OAB could lack clinical efficacy in neurogenic patients. Several systematic reviews have been published in the last 15 years to evaluate the evidence concerning the different treatments for neurogenic OAB (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In 2012, Madhuvrata and coworkers (2) published a systematic review and meta-analysis on anticholinergic treatment of adult neurogenic OAB, which updated and completed a previous systematic review assessing the efficacy and tolerability of anticholinergic agents in patients with OAB associated to multiple sclerosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis evaluated the results of studies focusing on sacral neuromodulation (SNM) in patients with neurogenic lower urinary tract dysfunction (8). Finally, several systematic reviews with metanalysis evaluated the treatment of overactive bladder syndrome with Botulinum toxin injection (9)(10)(11)(12)(13)(14)(15). Although a relevant bulk of information from previous systematic reviews is available, certain specific aspects, such as efficacy mirabegron and new anticholinergic agents in neurogenic bladder have not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Antimuscarinics and β3-adrenoceptor agonist can reduce detrusor overactivity and lower intravesical pressure [ 138 , 139 ]. The clinical efficacy of intravesical botulinum toxin A injection after failure of medication has been demonstrated [ 140 ]. Surgeries such as augmentation cystoplasty is indicated in patients’ refractory to conservative treatments.…”
Section: Discussionmentioning
confidence: 99%